The Effect of Formalin Concentration and Storage Duration on Elasticity, Tensile Strength, Fur Loss, and Water Absorption of Tanned Rabit Skin - Amertaningtyas, Dedes; Husna, Nissa’ul; Andriani, Ria Dewi; Wibowo, RLM. Satrio Ari; Nuraini, Eko (CV. Komunitas Dunia Peternakan, 2025)
Rabbit skin is one by-product that can be utilized for its aesthetic value through a tanning process so that the skin is resistant to destructive bacteria, namely Pseudomonas aeruginosa and Staphylococcus aureus. Furtigh is the strengthening of fur in the tanning process, in this research the furtigh process uses formalin so that rabbit fur is stronger and lasts longer. The purpose of this research was to determine the appropriate concentration of formalin and storage length used in rabbit fur tanning in the terms of pliability, tensile strength, fur loss and water absorption. The method used in this research is a laboratory experimental method using a Completely Randomized Design (CRD) with a nested design consisting of 4 treatment and repeated 4 times each. This treatment used formalin of 10%, 15%, 20% and 25%. Variables tested included pliability, tensile strength, fur loss and water absorption. Processing data using analyzed by Analysis of Variance (ANNOVA) and continued with the Duncan Multiple Range Test (DMRT). The results showed that different usage of formalin exerted significant influence (P<0,05) on the tear elasticity of tanned rabbit furs with a result of F1: 29,76%; F2: 32,85%; F3: 41,70%; F4: 41,88%. Different concentration usage of formalin have significant influence of tanned rabbit fur (P<0.05) on rabbit skin tensile strength fur tanning with a results of F1: 36.63 N/mm2; F2: 39.69 N/mm2; F3: 43.81 N/mm2; F4: 48.36 N/mm2. Fur loss test showed that the use of different formalin exerted highly significant influence (P<0.01) of tanned rabbit fur loss with a result of F1: 4.15; F2: 3.78; F3: 3.49; F4: 3.40. Water absorption test that the use of different formalin concentration have highly significant influence of tanned rabbit fur (P<0.01) with water absorption with a result of F1: 192.12%; F2: 217.95%; F3: 237.85%; F4: 238.27% on 2 hours of water absorption. Storage length did not have significant influence of tanned rabbit fur (P<0.05) on rabbit skin elasticity, tensile strength, fur loss and water absorption.